Making and remaking the Balkans nations and states since 1878 - Austin, Robert C. 1964- (University of Toronto Press, 2019)
"Each brief book in this highly curated series focuses on big ideas related to the Munk School of Global Affairs' key themes (including, for example, global innovation, global security, global justice, and the global economy). Munk Series titles highlight each author's unique voice, engaging curious readers with vivid narratives, insightful analysis, and lively prose. Books selected for the Munk Series are accessible and intellectually significant, meeting a rigorously high standard of scholarship. With more than 25 years since the collapse of communism, the end of the wars and billions of dollars in aid, the Balkans are still characterized by corruption, state capture, and decidedly unmodern states that are often either weak or authoritarian. Taking the contemporary Balkans as a starting point, Making and Remaking the Balkans studies the region's history combined with observations based on more than twenty years of field experience. Primarily concerned with current issues in the Balkans since 1989, this book explains why the region has endured such a prolonged and fraught transition to democracy and eventual membership in the European Union. The young and educated have largely left. Governmental crisis and economic stagnation is the norm and much-needed regional cooperation has been suppressed by renewed nationalism. Wars on corruption have proved to be largely rhetorical. Making and Remaking the Balkans offers a systematic study of the issues the entire region faces as it struggles to complete the European integration process at a time when the European Union faces bigger problems elsewhere."--
Keywords: Geschichte 1989-; Jugoslawienkriege; Demokratisierung; Politik; Kosovo-Krieg; Balkanhalbinsel; Balkan Peninsula / History / 1989-; Balkan Peninsula / Politics and government / 1989-; Politics and government; Balkan Peninsula; Since 1989; History